Brightening Tomorrow Together 2024 Proceedings of the Brightening Tomorrow Together 2024 Symposium and Industry Summit - Ting, David S-K; Vaselbehagh, Ahmad (Springer Proceedings in Energy, 2024)
XVI, 208 p. 96 illus., 82 illus. in color.